Processing and Outcome of Death Penalty Appeals After Furman v. Georgia, 1973-1995: (United States) - Fagan, Jeffrey ([Verlag nicht ermittelbar], 2002)
This data collection effort was undertaken to analyze the outcomes of capital appeals in the United States between 1973 and 1995 and as a means of assessing the reliability of death penalty verdicts (also referred to herein as "capital judgments" or "death penalty judgments") imposed under modern death-sentencing procedures. Those procedures have been adopted since the decision in Furman v. Georgia in 1972. The United States Supreme Court's ruling in that case invalidated all then-existing death penalty laws, determining that the death penalty was applied in an "arbitrary and capricious" manner and violated Eighth Amendment protections against cruel and unusual punishment. Data provided in this collection include state characteristics and the outcomes of review of death verdicts by state and year at the state direct appeal, state post-conviction, federal habeas corpus, and all three stages of review (Part 1). Data were compiled from published and unpublished official and archived sources. Also provided in this collection are state and county characteristics and the outcome of review of death verdicts by county, state, and year at the state direct appeal, state post-conviction, federal habeas corpus, and all three stages of review (Part 2). After designing a systematic method for identifying official court decisions in capital appeals and state and federal post-conviction proceedings (no official or unofficial lists of those decisions existed prior to this study), the authors created three databases original to this study using information reported in those decisions. The first of the three original databases assembled as part of this project was the Direct Appeal Database (DADB) (Part 3). This database contains information on the timing and outcome of decisions on state direct appeals of capital verdicts imposed in all years during the 1973-1995 study period in which the relevant state had a valid post-Furman capital statute. The appeals in this database include all those that were identified as having been finally decided during the 1973 to 1995 period (sometimes called "the study period"). The second original database, State Post-Conviction Database (SPCDB) (Part 4), contains a list of capital verdicts that were imposed during the years between 1973 and 2000 when the relevant state had a valid post-Furman capital statute and that were finally reversed on state post-conviction review between 1973 and April 2000. The third original database, Habeas Corpus Database (HCDB) (Part 5), contains information on all decisions of initial (non-successive) capital federal habeas corpus cases between 1973 and 1995 that finally reviewed capital verdicts imposed during the years 1973 to 1995 when the relevant state had a valid post-Furman capital statute. Part 1 variables include state and state population, population density, death sentence year, year the state enacted a valid post-Furman capital statute, total homicides, number of African-Americans in the state population, number of white and African-American homicide victims, number of prison inmates, number of FBI Index Crimes, number of civil, criminal, and felony court cases awaiting decision, number of death verdicts, number of Black defendants sentenced to death, rate of white victims of homicides for which defendants were sentenced to death per 100 white homicide victims, percentage of death row inmates sentenced to death for offenses against at least one white victim, number of death verdicts reviewed, awaiting review, and granted relief at all three states of review, number of welfare recipients and welfare expenditures, direct expenditures on the court system, party-adjusted judicial ideology index, political pressure index, and several other created variables. Part 2 provides this same state-level information and also provides similar variables at the county level. Court expenditure and welfare data are not provided in Part 2, however. Part 3 provides data on each capital direct appeal decision, including state, FIPS state and county code for trial court county, year of death verdict, year of decision, whether the verdict was affirmed or reversed, and year of first fully valid post-Furman statute. The date and citation for rehearing in the state system and on certiorari to the United States Supreme Court are provided in some cases. For reversals in Part 4 information was collected about state of death verdict, FIPS state and county code for trial court county, year of death verdict, date of relief, basis for reversal, stage of trial and aspect of verdict (guilty of aggravated capital murder, death sentence) affected by reversal, outcome on retrial, and citation. Part 5 variables include state, FIPS state and county codes for trial court county, year of death verdict, defendant's history of alcohol or drug abuse, whether the defendant was intoxicated at the time of the crime, whether the defense attorney was from in-state, whether the defendant was connected to the community where the crime occurred, whether the victim had a high standing in the community, sex of the victim, whether the defendant had a prior record, whether a state evidentiary hearing was held, number of claims for final federal decision, whether a majority of the judges voting to reverse were appointed by Republican presidents, aggravating and mitigating circumstances, whether habeas corpus relief was granted, what claims for habeas corpus relief were presented, and the outcome on each claim that was presented. Part 5 also includes citations to the direct appeal decision, the state post-conviction decision (last state decision on merits), the judicial decision at the pre-penultimate federal stage, the decision at the penultimate federal stage, and the final federal decision.